First evaluation of geopolymer encapsulation of simulated alkaline aluminum-rich liquid waste from Mo-99 production - Talavera Ramos, Whitney; Tellería Narváez, Adrián; Dos Santos, Lucas; Arcone, Daniel; Manzini, Ayelén (Frontiers in Nuclear Engineering, 2026)
This study investigates the synthesis and characterization of metakaolin-based geopolymers for the immobilization of simulated aluminum-containing radioactive liquid waste. Two kaolin precursors with different Si/Al ratios and purities were calcined between 700 °C and 900 °C. Geopolymers were prepared using a sodium silicate–NaOH activating solution (10 M NaOH) with and without sand, and cured at 60 °C. The effects of curing time and simulated liquid waste incorporation (10–40 wt%) on mechanical strength and microstructural development were evaluated through compressive strength tests, XRD, and SEM analyses. The results showed that curing time influenced strength development. Incorporation of simulated liquid waste generally reduced compressive strength, probably due to increased porosity and decreased metakaolin (MK) dissolution; however acceptable performance was achieved at a 20 wt% addition for MKSR-based geopolymers. XRD analyses confirmed the formation of an amorphous band between 25° and 35° typical of geopolymer structures. In contrast, MKS-based geopolymers exhibited lower mechanical strength and incomplete gel formation under the tested conditions. These findings demonstrate the potential of local precursor MKSR metakaolin-based geopolymers as promising matrices for the immobilization of aluminum-bearing radioactive liquid waste.